2014
DOI: 10.1039/c4nr00316k
|View full text |Cite
|
Sign up to set email alerts
|

Grating-structured metallic microsprings

Abstract: We fabricate grating-structured metallic microsprings with well-defined helical angles and diameters, which are self-rolled from strained nanomembranes patterned with gratings. The grating structures on the metal membrane, replicated from the imprinted polymer layer beneath, give rise to the controlled rolling direction after selective etching of the underlying sacrificial layer. The rolling direction of the grating-structured thin metal film is always perpendicular to the long side edge of gratings, offering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Helical structures have been widely used in industry due to their low stiffness and superior capability to resist large axial strain, while helical structures are also the fundamental configuration for DNA and many other biomolecules. Three-dimensional helical nanostructures of zinc oxide (ZnO) have also been investigated, such as nanohelices [ 1 , 2 , 3 ], nanorings formed by self-coiling nanobelts [ 4 , 5 ], and nanosprings [ 6 , 7 , 8 ]. ZnO helical nanostructures showed superelastic behavior, and their spring constant increased continuously up to 300–800% when they were stretched [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Helical structures have been widely used in industry due to their low stiffness and superior capability to resist large axial strain, while helical structures are also the fundamental configuration for DNA and many other biomolecules. Three-dimensional helical nanostructures of zinc oxide (ZnO) have also been investigated, such as nanohelices [ 1 , 2 , 3 ], nanorings formed by self-coiling nanobelts [ 4 , 5 ], and nanosprings [ 6 , 7 , 8 ]. ZnO helical nanostructures showed superelastic behavior, and their spring constant increased continuously up to 300–800% when they were stretched [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These differences in stress can arise through differences in processing or material CTE. In a single layer with a stress gradient developed during processing, the differential expansion between the top and bottom can create a 3D shape upon release, a technique that has been used to create helices and other complex arcs . A bilayer or multilayer stack, for instance of a highly compressed oxide stacked atop a less compressed or even tensile metal, will also create a 3D arc when released .…”
Section: Actuation Mechanismsmentioning
confidence: 99%
“…[38,58,[175][176][177] The rolling direction can be controlled by experimental parameters and surface structures. [103,178,179] Meanwhile, the diameter of the tubular structure is determined by the strain gradient and mechanical property of the material and thus can be tuned correspondingly. [173] The rolled-up technology has made many 3D structures with cylindrical symmetry from a lot of materials and material combinations.…”
Section: Rolled-up Nanomembranes For 3d Devicesmentioning
confidence: 99%
“…Previous investigations demonstrated that the strain gradient can be experimentally introduced by utilizing lattice mismatch, altering parameters during deposition of nanomembrane, fabricating nanoparticles with surface tension, etc . The rolling direction can be controlled by experimental parameters and surface structures . Meanwhile, the diameter of the tubular structure is determined by the strain gradient and mechanical property of the material and thus can be tuned correspondingly .…”
Section: Nanomembrane Origamimentioning
confidence: 99%